Toxic Effects of Lead Exposure on Freshwater Climbing Perch, Anabas testudineus, and Bioremediation Using Ocimum sanctum Leaf Powder - Nimai Chandra Saha; Arnab Chatterjee; Priyajit Banerjee; Ritwick Bhattacharya; Auroshree Sadhu; Paolo Pastorino; Shubhajit Saha (Toxics)
The acute and chronic toxicity of lead to Anabas testudineus was determined in this study using static replacement bioassay testing. During the chronic toxicity studies, an experiment on the bioremediation of lead toxicity using Ocimum sanctum leaf powder was conducted. The 96 h LC50 values of lead for Anabas testudineus was 1.08 mg/L. Different biomarkers, such as the hepatosomatic index, gonadosomatic index, and fecundity, were significantly lower in fish subjected to 10% and 20% of the 96 h LC50 values of lead, compared to controls. The 45-day chronic exposure of fish to lead concentrations of 0.2 mg/L and above significantly lowered the number of total RBC, hemoglobin content, HCT (%), plasma protein, and cholesterol while decreasing the level of total WBC, plasma glucose, creatinine, serum AST and serum ALT. The leaf powder of Ocimum sanctum plays a significant role in ameliorating lead toxicity.